Performance management of generalist care for hospitalised multimorbid patients—a scoping review for value-based care - Khoo, Jia En Joy; Lim, Cher Wee; Lai, Yi Feng (Frontiers in Health Services, 2024)
Objectives Given the shift towards value-based healthcare and the increasing recognition of generalist care, enacting value-based healthcare for generalist care is critical. This work aims to shed light on how to conduct performance management of generalist care to facilitate value-based care, with a focus on medical care of hospitalised patients. Design and setting A scoping review of published literature was conducted. 30 publications which were relevant to performance management of generalist medical inpatient care were included in the review. Outcome measures The performance measures used across the studies were analysed and other qualitative findings were also obtained. Results We report an overall lack of research on performance management methods for generalist inpatient care. Relevant performance measures found include both outcome and process of care measures and both clinical and reported measures, with clinical outcome measures the most frequently reported. Length of stay, readmission rates and mortality were the most frequently reported. The insights from the papers emphasise the relevance of process of care measures for performance management, the advantages and disadvantages of types of measures and provide suggestions relevant for performance management of generalist inpatient care. Conclusion The findings of this scoping review outline a variety of performance measures valuable for generalist inpatient care including clinical outcome measures, reported outcome measures and process of care measures. The findings also suggest directions for implementation of such performance management, including emphasis on physician level performance management and the importance of documentation training. Further research for selecting and operationalising the measures for specific contexts and developing a comprehensive performance management system involving these measures will be important for achieving value-based healthcare for generalist inpatient care.